2005
DOI: 10.1111/j.1540-8159.2005.09753.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supraventricular Tachycardias on Driving Ability in Patients Referred for Radiofrequency Catheter Ablation

Abstract: SVT frequently occurs during driving and is often associated with hemodynamic symptoms including near-syncope and syncope. Women reported tachycardia-related hemodynamic symptoms more often than men. There is a correlation between having experienced near-syncope and considering tachycardia as an obstacle to driving. The risk for serious tachycardia-related symptoms should be considered, especially in occupational drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…In a study on the relationship of SVT with driving, 57% of patients with SVT experienced an episode while driving, and 24% of these considered it to be an obstacle to driving (29). This sentiment was most common in patients who had experienced syncope or near-syncope.…”
Section: Clinical Presentation and Differential Diagnosis On The Basimentioning
confidence: 98%
“…In a study on the relationship of SVT with driving, 57% of patients with SVT experienced an episode while driving, and 24% of these considered it to be an obstacle to driving (29). This sentiment was most common in patients who had experienced syncope or near-syncope.…”
Section: Clinical Presentation and Differential Diagnosis On The Basimentioning
confidence: 98%
“…Symptoms such as fatigue, dizziness, and cold sweat are common and may contribute to a feeling of insecurity because of arrhythmia problems and lead to self-imposed restrictions in a person's daily life. [5][6][7]31 A study describing patients with SVT showed that as many as 50% had been near syncope while having h e a r t & l u n g 4 0 ( 2 0 1 1 ) 4 0 5 e4 1 1 a tachycardia attack and 14% had experienced syncope. 6 In a qualitative study, Wood et al 8 described the situation of patients with SVT.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7]31 A study describing patients with SVT showed that as many as 50% had been near syncope while having h e a r t & l u n g 4 0 ( 2 0 1 1 ) 4 0 5 e4 1 1 a tachycardia attack and 14% had experienced syncope. 6 In a qualitative study, Wood et al 8 described the situation of patients with SVT. The patients lived with uncertainty, never knowing when to expect the next attack.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Themes identified in our data demonstrate that at least for some patients, arrhythmias have a significant negative effect on their lives; leads to a perceived reduction in overall quality of life; impacts all aspects of their life: work, social, and daily activities; results in almost constant fear and anxiety; and requires enormous time to search for support and information. Walfridsson and colleagues [25] also noted SVT patients’ decreased engagement with social activities. Research has also found patients with SVT [26] and AF [27] report feeling uninformed, unsupported, and distressed.…”
Section: Discussionmentioning
confidence: 99%